2006
DOI: 10.1051/animres:2006029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a reduction of diet crude protein content on gaseous emissions from deep-litter pens for fattening pigs

Abstract: -Two successive batches of 32 fattening pigs per batch were each divided into 2 homogenous groups of 16 pigs fed either a high crude protein (CP) level diet (HP-groups) or a low crude protein level diet balanced with synthetic amino acids (LP-groups). Pigs were raised on strawbased deep litters in separate rooms according to diets. Once a month, the emissions of ammonia (NH 3 ), nitrous oxide (N 2 O), methane (CH 4 ), carbon dioxide (CO 2 ) and water vapour (H 2 O) were measured continuously for 6 days consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
1
19
0
2
Order By: Relevance
“…With a sawdust bedding, Groenestein and Van Faassen (1996) measured N emissions, as NH 3 and N 2 O, of 2.9 to 4.8 and, 4.8 to 7.2 g/pig per day, respectively. A higher NH 3 emission (12.5 g/pig per day) and a lower N 2 O emission (0.80 g/pig per day) were measured by Philippe et al (2006) for straw bedding. Ammonia emission from the outdoor exercise area was not measured in the present experiment.…”
Section: Discussionmentioning
confidence: 85%
“…With a sawdust bedding, Groenestein and Van Faassen (1996) measured N emissions, as NH 3 and N 2 O, of 2.9 to 4.8 and, 4.8 to 7.2 g/pig per day, respectively. A higher NH 3 emission (12.5 g/pig per day) and a lower N 2 O emission (0.80 g/pig per day) were measured by Philippe et al (2006) for straw bedding. Ammonia emission from the outdoor exercise area was not measured in the present experiment.…”
Section: Discussionmentioning
confidence: 85%
“…On slatted floor, cited values range from 5 g to 15 g NH 3 -N/day per sow (Groot Koerkamp et al, 1998;Groenestein et al, 2003). Whatever the floor type, numerous factors can influence NH 3 -emissions, like feeding management, interior climate, season and waste treatment (Harper et al, 2004;Philippe et al, 2006 and. Furthermore, for litter systems, properties of bedding materials carbon/nitrogen ratio (C/N ratio; carbon availability, pH value and physical structure, among others) affect volatilization (Jeppsson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Külling et al (2001) reported decreased N 2 O emissions from storage manure of dairy cows fed lowprotein diets, but the total GHG emissions were not affected as there was an increased CH 4 emission from the low protein manure. Velthof et al (2005) observed large decrease in the NH 3 and CH 4 emissions during manure storage and N 2 O emission from soilby by decreasing the protein content of swine diets whereas reverse effect on N 2 O emissions was reported in swine (Philippe et al, 2006) and dairy cattle (Arriaga et al, 2010) on lowering the dietary protein. Shifting N losses from urine to faeces is expected to reduce N 2 O emissions from manure applied soil due to the lower concentration of NH 4 + in manure.…”
Section: Species and Individual Variationmentioning
confidence: 94%